How to manage chronic urticaria 'beyond' guidelines: a practical algorithm. Issue 6 (June 2017) - Rutkowski, K.; Grattan, C. E. H.
Summary: Chronic urticaria (CU) is a disease characterized by pruritic weals, angio‐oedema or both occurring for at least 6 weeks. It encompasses spontaneous and inducible urticarias. The national and international guidelines outline the principles of treatment. Omalizumab, an anti‐immunoglobulin E monoclonal antibody, has transformed the management of many severe and treatment‐refractory patients. However, current UK guidance on its use does not address the needs of those with less severe disease, inducible urticarias, idiopathic histaminergic angio‐oedema without weals as a presentation of CU and omalizumab non‐responders. Our algorithm and a summary of the evidence to support its principles offers guidance and a more systematic targeted approach to using a range of 'off‐label' agents for specific phenotypes of CU. It will be of use when guideline‐recommended mast cell mediator antagonists fail to control symptoms and/or using omalizumab is ineffective, not practical or unfunded.